Development of a tag-free plant-made interferon gamma production system with improved therapeutic efficacy against viruses - Jiang, Min-Chao; Hsu, Wei-Li; Tseng, Ching-Yu; Lin, Na-Sheng; Hsu, Yau-Heiu; Hu, Chung-Chi (Frontiers in Bioengineering and Biotechnology, 2024)
Plants offer a promising platform for cost-effective production of biologically active therapeutic glycoproteins. In previous studies, we have developed a plant expression system based on Bamboo mosaic virus (BaMV) by incorporating secretory signals and an affinity tag, which resulted in notably enhanced yields of soluble and secreted fusion glycoproteins (FGs) in N. benthamiana. However, the presence of the fusion tags on the recombinant glycoproteins is undesirable for biomedical applications. This study aimed to develop a refined expression system that can efficiently produce tag-free glycoproteins in plants, with enhanced efficacy of mature interferon gamma (mIFNγ) against viruses. To accommodate the specific requirement of different target proteins, three enzymatically or chemically cleavable linkers were provided in this renovated BaMV-based expression system. We demonstrated that Tobacco etch virus (TEV) protease could process the specific cleavage site (LTEV) of the fusion protein, designated as SSExtHis(SP)10LTEV-mIFNγ, with the optimal efficiency under biocompatible condition to generate tag-free mIFNγ glycoproteins. The TEV protease and secretory-affinity tag could be effectively removed from the target mIFNγ glycoproteins through a Ni2+-NTA chromatography. In addition, the result of anti-viral assay showed that the tag-free mIFNγ glycoproteins exhibited enhanced biological properties against Sindbis virus, with comparable antiviral activity of the commercialized HEK293-expressed hIFNγ. Thus, the improved BaMV-based expression system developed in this study may provide an alternative strategy for producing tag-free therapeutic glycoproteins intended for biomedical applications.